Performance of construction company listed in Kuala Lumpur Stock Exchange - Liow, Raymond Sang Loong (2010)
This research measures and analyses the performance of construction company listed in Kuala Lumpur Stock Exchange for year 2008 and 2009. The performance is compared with Earnings Per Share (EPS), Quick Ratio, Current Ratio, Return On Equity (ROE), Return On Assets (ROA), and Profit Margin. The main aim of this study is to study the stock performance of Kuala Lumpur Stock Exchange. The minor aims of this study are to identify the listed construction company in Kuala Lumpur Stock Exchange (focus on construction company in Malaysia) and to analyze the healthiness of the public listed construction company.In order to achieve the objectives of this study, the scope of this study will be focusing on a few listed construction companies in Malaysia. The scopes of the data collection in this study focus the successful of construction companies and the selected construction companies must have their own management properties such as their background, asset and others. Data were collected from Kuala Lumpur Stock Exchange and construction companies annual reports. Microsoft Excel spreadsheets were used to calculate and analyze the data.